The Effectiveness of a Mathematics Textbook Embedded with Mpu Kuturan’s Values on Prospective Elementary Teachers’ Numeracy Skills - I Komang Wahyu Wiguna; Ni Nyoman Lisna Handayani; I Komang Sesara Ariyana (Universitas Pendidikan Ganesha, 2025)
The numeracy skills of prospective elementary school teachers remain relatively low and are often not contextualized with relevant local values in the learning process. This study aims to analyze the effectiveness of a mathematics textbook infused with Mpu Kuturan's values in improving numeracy skills among prospective elementary school teachers. A quasi-experimental design was employed, using a nonequivalent group pretest-posttest model. The research subjects consisted of 56 PGSD students who were enrolled in the Mathematics Education course. Data were collected using a validated numeracy test and analyzed quantitatively through t-tests. The results showed an increase in the average numeracy score from 62.45 (pretest) to 81.23 (posttest), with the t-test indicating a significance value of 0.000 (<0.05), confirming a statistically significant improvement. These findings indicate that integrating local values into mathematics teaching materials enhances not only cognitive aspects but also reinforces relevant cultural values in the learning process. This study recommends the development of contextual learning materials based on local wisdom as an innovative strategy in teacher education.